Advances in pharmacotherapy for diabetic foot osteomyelitis. (2nd November 2021) - Ahluwalia, Raju; Lázaro-Martínez, Jose Luiz; Reichert, Ines; Maffulli, Nicola
ABSTRACT: Introduction : The diagnosis of diabetic foot osteomyelitis (DFO) is usually clinical. Its severity is related to the location and depth of the lesion, and the presence of necrosis or gangrene. The aetiology of diabetic foot osteomyelitis (DFO) is usually polymicrobial, and DFO is often associated with chronic or recurring ulceration. Areas covered : We built on the International Working Group on the Diabetic Foot (IWGDF) guidelines on the management of diabetic foot infection, providing an outline of the current and new concepts in pharmacotherapy in DFO. We assess future strategies in both medical, surgical and combination management of DFO. Expert opinion : Surgical removal of infected bone is considered as the standard treatment, but a medical approach of certain selected situations has now proven efficacy in selected patients. The combination of new modalities in local antibiotic delivery may provide better long-term solutions and more lasting remission and avoid the disadvantages of prolonged systemic antibiotics.